2016
DOI: 10.26811/peuradeun.v4i1.89
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Employees and Impact on Promotion of Position

Abstract: Performance appraisal is an activity controlling the management of a company. This study is an empirical study that aims to determine the effect of performance appraisal and promotion of their work motivation and their impact on employee performance at Serambi Mekkah University. The research was conducted at Serambi Mekkah University. The populations in this study were all employees at Serambi Mekkah University which amounts to 105 people. Data was collected by distributing questionnaires. Primary data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Promosi diberikan untuk memotivasi semangat kerja karyawan, karyawan yang dipromosikan akan memiliki tanggung jawab yang lebih besar, martabat atau status yang lebih tinggi, dan diharapkan memiliki keterampilan yang lebih baik (Rinaldi dkk., 2018) Keputusan promosi jabatan tidak hanya penting untuk karier karyawan, namun juga untuk meningkatkan kepuasan kerja (Busswolder et al, 2019). Para pemimpin harus menyadari pentingnya promosi dalam meningkatkan kinerja karyawan harus dipertimbangkan secara objektif (Sarboni, 2016) . Jika pemimpin sudah sadar untuk mempertimbangkan promosi secara objektif, maka perusahaan akan terhindar dari masalah yang menunda peningkatan output dan itu bisa merugikan perusahaan seperti: ketidakpuasan karyawan, keluhan, kurangnya semangat kerja, menurunnya disiplin kerja, dan banyak dari mereka absen atau bahkan masalah mogok kerja (Sarboni, 2016).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Promosi diberikan untuk memotivasi semangat kerja karyawan, karyawan yang dipromosikan akan memiliki tanggung jawab yang lebih besar, martabat atau status yang lebih tinggi, dan diharapkan memiliki keterampilan yang lebih baik (Rinaldi dkk., 2018) Keputusan promosi jabatan tidak hanya penting untuk karier karyawan, namun juga untuk meningkatkan kepuasan kerja (Busswolder et al, 2019). Para pemimpin harus menyadari pentingnya promosi dalam meningkatkan kinerja karyawan harus dipertimbangkan secara objektif (Sarboni, 2016) . Jika pemimpin sudah sadar untuk mempertimbangkan promosi secara objektif, maka perusahaan akan terhindar dari masalah yang menunda peningkatan output dan itu bisa merugikan perusahaan seperti: ketidakpuasan karyawan, keluhan, kurangnya semangat kerja, menurunnya disiplin kerja, dan banyak dari mereka absen atau bahkan masalah mogok kerja (Sarboni, 2016).…”
Section: Pendahuluanunclassified
“…Para pemimpin harus menyadari pentingnya promosi dalam meningkatkan kinerja karyawan harus dipertimbangkan secara objektif (Sarboni, 2016) . Jika pemimpin sudah sadar untuk mempertimbangkan promosi secara objektif, maka perusahaan akan terhindar dari masalah yang menunda peningkatan output dan itu bisa merugikan perusahaan seperti: ketidakpuasan karyawan, keluhan, kurangnya semangat kerja, menurunnya disiplin kerja, dan banyak dari mereka absen atau bahkan masalah mogok kerja (Sarboni, 2016).…”
Section: Pendahuluanunclassified
“…Performance is the result of a person as a whole during a certain period in carrying out tasks, such as work standards, targets or target criteria that have been determined beforehand and have been mutually agreed upon. Employee performance requires appraisal and making formal and informal oral and written presentations to various audiences in various occupations in the workforce (Sarboini, 2016). This is intended to provide a good opportunity for employees to their career plans in terms of strengths and weaknesses so that the organization can determine salary payments, provide promotions, and see employee behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On the other hand, if staffs have loyalty toward the institution, they will have more confidence in their job and it will create a positive impact on their satisfaction (Turkyilmaz, Akman, & Pastuszak, 2011;Walidin, 2016;Chen, Tsui, & Farh, 2002). Many scholars have studied the role of employee satisfaction on employee loyalty and concluded that employee satisfaction influences employee loyalty positively (Petty, Brewer, & Brown, 2005;Aityan & Gupta, 2011;Sarboini, 2016).…”
Section: Job Satisfaction and Employee Loyaltymentioning
confidence: 99%